Napovedniki gibljivosti pri mladinskih nogometaših: kontekstualizacija vpliva biološke zrelosti - Veršic, S.; Foretic, N.; Spasic, M.; Uljevic, O. (Kinesiologia Slovenica, 2020)
This study aimed to evaluate factors that influence soccer-specific change-of-direction speed (SSCODS) and reactive agility (SSRAG) in youth soccer players, taking into account their biological-maturity. The sample comprised 41 youth soccer players (14-15, height: 167.1±8.7 cm, mass: 56.1±4.9 kg) tested on anthropometrics, 10m-sprint, countermovement jump, reactive-strength-index, 20-yard generic test [20-yard], SSCODS and SSRAG. The biological-maturity was calculated on the basis of peak-height-velocity and expressed as maturity-offset (MO). The significant correlations between MO with remaining variables were evidenced, and the highest correlations were noted for CMJ and the 20-yard generic CODS test (Pearson`s r = 0.61 and -0.63, p < 0.01; respectively). Multiple regression analyses were performed for 20-yard, SSCODS, and SSRAG as criteria. Predictors explained 66% percent of the 20-yard- and 40% of the SSCODS-variance (both p < 0.05). The biological-maturity has a minimal influence on performances where coordination, cognitive and perceptual capacities are important determinants of achievement.